(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
The essay focuses on the intersection between the art of preaching and Creole identity in the 17th-century Hispanic World. I study the life and works of Andrés Ferrer de Valdecebro, a Dominican priest who was born in Spain and lived in Mexico for more than ten years. Specifically, I will analyze the way in which this author reflects on the connections between the practices of preaching and the foundation of a Creole imaginary. I will demonstrate how this plural, heterogeneous, and polyphonic process that we now know as the creation of a Creole view developed from multiple and unstable discursive positions.